Spinal cord injury impairs neurogenesis and induces glial reactivity in the hippocampus - Jure, Ignacio (2017)
The incorporation of newborn neurons with increased synaptic remodeling and activity-dependent plasticity in the dentate gyrus enhances hippocampal-dependent learning performances. Astrocytes and microglial cells are components of the neurogenic niche and regulate neurogenesis under normal and neurophatological conditions leading to functional consequences for learning and memory. Although cognitive impairments were reported in patients after spinal cord injury (SCI), only few studies have considered remote changes in brain structures which are not related with sensory and motor cortex. Thus, we examined neurogenesis and glial reactivity by stereological assessment in dentate gyrus sub-regions after three different intensities of thoracic spinal cord compression in rats. Sixty days after injury we observed a decrease in the Basso–Bresnahan–Beattie locomotor scale scores, rotarod performance and volume of spare tissue that correlated with the severity of the compression. Regarding the hippocampus, we observed that neurogenesis and hilar neurons were reduced after severe SCI, while only neurogenesis decreased in the moderately injured group. In addition, severe SCI induced reactive microglia and astrogliosis in all dentate gyrus sub-regions. Furthermore, the density of reactive microglia increased in the hilus whereas astrogliosis developed in the molecular layer after moderate SCI. No changes were observed in the mildly injured rats. These results suggest glial response and neurogenesis are associated with injury intensity. Interestingly, hippocampal neurogenesis is more sensitive to SCI than astrocytes or microglia reaction, as moderate injury impairs the generation of new neurons without changing glial response in the subgranular zone.